Empowering Mathematical Problem Solving in Elementary Classrooms: Challenges and Opportunities in Society 5.0 - Eliva Sukma Cipta; Nurainiyah Nurainiyah; Neneng Sulastri; Usep Suherman; Dick Dick Maulana (Al Ibtida: Jurnal Pendidikan Guru MI, 2025)
AbstractThe Society 5.0 era demands the world of education to equip students with critical, creative, and solution-oriented thinking skills in dealing with real problems. This study aims to explore the level of elementary school students' mathematical problem-solving abilities and identify the challenges and opportunities faced by teachers in building these skills in the Society 5.0 era. This study uses a mixed method approach with a sequential explanatory model. Quantitative data were obtained through problem-solving tests given to 60 fifth-grade students from two public elementary schools in Bandung Regency who were selected using stratified random sampling. The results showed that students' problem-solving abilities were in the moderate category (average = 21.6 out of a maximum score of 32), with the highest performance at the "implementing the plan" stage and the lowest at the "re-checking" stage. Qualitative data was obtained through interviews and observations of four mathematics teachers. Thematic analysis revealed challenges in the form of limited time, reflective materials, and the use of technology. However, teachers also saw opportunities through contextual approaches and digital platforms. These results demonstrate the importance of innovative, reflective, and technology-integrated mathematics learning designs to equip students with 21st-century skills.Keywords: problem solving, elementary classrooms, society 5.0.AbstrakEra Society 5.0 menuntut dunia pendidikan untuk membekali peserta didik dengan keterampilan berpikir kritis, kreatif, dan berorientasi solusi dalam menghadapi permasalahan nyata. Penelitian ini bertujuan untuk mengeksplorasi tingkat kemampuan pemecahan masalah matematika siswa sekolah dasar dan mengidentifikasi tantangan serta peluang yang dihadapi guru dalam membangun keterampilan tersebut di era Society 5.0. Penelitian ini menggunakan pendekatan metode campuran dengan model eksplanatori sekuensial. Data kuantitatif diperoleh melalui tes pemecahan masalah yang diberikan kepada 60 siswa kelas V dari dua sekolah dasar negeri di Kabupaten Bandung yang dipilih menggunakan stratified random sampling. Hasil penelitian menunjukkan bahwa kemampuan pemecahan masalah siswa berada pada kategori sedang (rata-rata = 21,6 dari skor maksimum 32), dengan kinerja tertinggi pada tahap "melaksanakan rencana" dan terendah pada tahap "memeriksa ulang". Data kualitatif diperoleh melalui wawancara dan observasi terhadap empat guru matematika. Analisis tematik mengungkap tantangan berupa keterbatasan waktu, materi reflektif, dan penggunaan teknologi. Namun, guru juga melihat peluang melalui pendekatan kontekstual dan platform digital. Hasil-hasil ini menunjukkan pentingnya desain pembelajaran matematika yang inovatif, reflektif, dan terintegrasi dengan teknologi untuk membekali siswa dengan keterampilan abad ke-21.Kata kunci: pemecahan masalah, sekolah dasar, society 5.0.